Adubação fosfatada no desenvolvimento de Hemerocallis fulva L. - Chaim Jardim Rosa, Yara Brito; Silva, Eulene Francisco da; Monaco, Kamila de Almeida [UNESP]; Ensinas, Simome Candido; Rosa Junior, Edgard Jardim; Chaim Jardim Rosa, Derek Brito (Universidade Estadual de Londrina (UEL), 2013)
In clayey Oxisol from the Brazilian Cerrado, where there is high P fixation, the phosphorus fertilization is necessary to increase the growth and flowering of ornamental plants. Thus, the objective of this study was to analyze the development of Hemerocallis as affected by phosphorus application in clayey Oxisol (Typic Haplustox). The experiment was conducted at the Gardening area of University Federal of Grande Dourados (UFGD) in Dourados-MS, Brazil. The experimental design was a randomized block with four replications. The treatments consisted of four P2O5 rates (0, 250, 500, 1000 kg ha(-1)) using simple superphosphate as source. The experimental unit was composed of one Hemerocallis fulva 'Flore Pleno' plant, grown in a plastic pot (5 liters). Phosphorus fertilization increased linearly the concentration of phosphorus in the soil; the plant had maximum absorption (5.26 g kg(-1)) with the calculated dose of 727 kg ha(-1) P2O5. H. fulva has a root system that develops best under high availability of P, however, for aerial part, the maximum of shoots fresh mass (451.1 g) was obtained with 427 kg ha(-1) of P2O5. Number of flower buds, flower diameter and height flower stalks were higher in the presence of phosphorus.
Phosphorus fertilization on the development of Hemerocallis fulva L.
Keywords: Herbaceous perennial; phosphorus; floriculture